2017
DOI: 10.1051/e3sconf/20171401052
|View full text |Cite
|
Sign up to set email alerts
|

The cooling effect by adsorption-desorption cycles

Abstract: Abstract. Adsorption appliances may turn out to be an alternative to compression-type refrigerators. The adsorption refrigeration machine may be driven by a low-grade heat source, especially solar energy. Solar adsorption cooling systems are environment-friendly and have zero ozone depletion potential. Therefore, the adsorption refrigeration is one kind of energy saving refrigeration methods. The merits of the adsorption refrigeration systems will be more significant especially when it is used in vehicles (aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…With the progress of the SACS technology, some silica gel-water adsorption chillers machines have been commercialized successfully on the market. 39 Different new adsorbent materials such as aluminum fumarate, activated alumina, and metalorganic frameworks (MOFs) [40][41] and new cycles of three and four beds 42 were investigated by several recent studies.…”
Section: Introductionmentioning
confidence: 99%
“…With the progress of the SACS technology, some silica gel-water adsorption chillers machines have been commercialized successfully on the market. 39 Different new adsorbent materials such as aluminum fumarate, activated alumina, and metalorganic frameworks (MOFs) [40][41] and new cycles of three and four beds 42 were investigated by several recent studies.…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption material goes further to be the core of the sorption system in most energy storage systems. Moreover, the cost, efficiency and the repeatability, toxicity, thermal stability and environmental friendliness of the adsorbent material affects the commercialization of the system [6,7]. Adsorbent materials are usually grouped into chemical, physical and composite adsorbents.…”
Section: Introductionmentioning
confidence: 99%
“…Physical adsorbents are the most used and researched adsorbents for sorption energy storage, although their performance in terms of energy density and thermal power delivered is much lower than that of chemical adsorbents. Some physical adsorbents include silica gel, activated alumina, activated carbon and molecular sieves; a physical adsorbent such as zeolite can have power delivered to almost the same level as that of chemical adsorption [7,11].…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption device utilised for the adsorptiondesorption process is a fin-tube heat exchanger in which the adsorbent materials are housed. The adsorption system are commercially used in countries like Japan, Germany, France, United States and China [7]. Water is generally preferred as the adsorbate for the 2 adsorption chiller because it is non-toxic, easily available and has a high evaporation enthalpy [8].…”
Section: Background and Motivationmentioning
confidence: 99%
“…7 shows the water adsorption kinetics of MOFs measured at the operating pressure and temperature condition for low heat adsorption cooling system (P = 1 kPa, T = 25 °C for adsorption and P = 5 kPa, T = 60 °C for desorption) as a function of time up to 3000 s. At 25 °C, it is observed that Al Fum captures the faster kinetics among the MOF samples under the working condition of same temperature and pressure. This may be due to the higher distribution of micro pores, which allows more water vapour to be adsorbed at low pressure, filling up the micro pore volume.…”
mentioning
confidence: 99%